2017
DOI: 10.1097/md.0000000000007654
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study to evaluate the efficacy of EGF, FGF-2, and 0.3% (w/v) ofloxacin drops on eardrum regeneration

Abstract: Background:Traumatic tympanic membrane perforations (TMPs) tend to spontaneous healing, however, large TMPs usually fail to healing. Clinical and experimental studies had demonstrated that growth factors accelerated the healing of large TMPs. The aim of this study was to compare the effects of growth factors and 0.3% (w/v) ofloxacin drops n the healing of human large TMPs.Methods:A total of 184 human large traumatic TMPs were randomly assigned to receive epidermal growth factor (EGF) treatment, fibroblast grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 38 publications
(50 reference statements)
0
29
0
Order By: Relevance
“…Perforations in three studies (6,13,23) were chronic due to various causes, while perforations in the other studies (7,(14)(15)(16)(17)(18)(19)(20)(21)(22)24) were caused by trauma. All studies reported the closure rates (6,7,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24); only eight studies reported the healing time (7,15,(18)(19)(20)(21)(22)24). Six studies provided the outcomes of hearing (7,14,15,19,21,24).…”
Section: Characteristics Of the Studiesmentioning
confidence: 95%
See 4 more Smart Citations
“…Perforations in three studies (6,13,23) were chronic due to various causes, while perforations in the other studies (7,(14)(15)(16)(17)(18)(19)(20)(21)(22)24) were caused by trauma. All studies reported the closure rates (6,7,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24); only eight studies reported the healing time (7,15,(18)(19)(20)(21)(22)24). Six studies provided the outcomes of hearing (7,14,15,19,21,24).…”
Section: Characteristics Of the Studiesmentioning
confidence: 95%
“…Of the 91 studies identified, a total of 14 studies with 1,072 patients were included in this meta-analysis, consisting of seven RCTs (7,14,15,17,19,23,24) and seven non-RCTs (6,13,16,18,(20)(21)(22). The included studies were published between 2003 and 2018, with a range of follow-up time from 3 to 12 months.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations